Research on the design of small interior space - Li, Zeting; Wu, Jiahao (E3S web of conferences, 2021)
In such a high population density society as China, especially in developed cities, the real estate market needs a concept of micro-housing. Working people in big cities like Beijing and Shanghai spend very little time at home while working and socializing outside the home every day. High-density population cities need to meet the living needs of as many people as possible in a limited area. If we can solve this problem the demand for houses will decrease and prices will fall. And tiny buildings can also reduce greenhouse gas emissions. (Statistics show that residential, commercial, and industrial buildings account for 40 percent of greenhouse gas emissions.) The ecological benefits of micro buildings extend beyond the house itself. Micro buildings not only increase the density of housing, so that more people have a home, but also shorten the time of transportation. After consulting a large number of literatures, this study hopes to summarize the existing literatures and find the best way for micro buildings to meet the needs of more people in high-density population cities. In this study, conclude some interior design methods or techniques to find out how to improve the quality of small space design. We search and review information in three different fields: indoor thermal comfort, human-based furniture, and interior lighting design. The paper presents some techniques including thermal control equipment and a day-light prediction system. Different human-based furniture is divided into various types, we analyse their advantages and disadvantages, leading to the small interior space to find how can they be used to improve human’s feeling. We discuss the possibility that designers enhance people’s life in a big city by using indoor designing ways.